Diversity and inclusion in organizations - Mitchell, Rebecca (Henry Stewart Talks, 2017)
Defining diversity, Potential impact of diversity, Perspectives on diversity, Information resource perspective, Social identity perspective, Managing diversity, Defining inclusion, Potential impact of inclusion, Increasing inclusion, Inclusive leadership